Prevalence and Determinants of Central Obesity at Urban Slum Dwellers in North Jakarta - Yunisa Astiarani; Maria G.A.I. Kedang; Nur Fitriah; Fani A. Chandra (Faculty of Public Health, Sriwijaya University, 2022)
Central obesity, widely known as a major cardiovascular disease risk factor, threatens the urban poor more than other socio-economic groups. The study intended to disclose the prevalence and determinants of central obesity in urban slum dwellers in North Jakarta. We conducted a survey study on residents aged 15 and above. The study randomly recruited two hundred forty-eight residents for direct interviews and body measurements according to the minimum sample requirement. Sociodemographic and Noncommunicable Diseases (NCDs) risk factors questionnaires were used and asked after weight, height, and waist circumference measurements. Descriptive and multivariate analyses were conducted to determine the central obesity prevalence and associated determinants. The central obesity prevalence in urban slum dwellers reaches 68.1%, presiding in women (69.4%) than men (65.3%). The multivariate binary logistic regression analysis indicates that central obesity was higher in the 30-59 y.o age group (Prevalence Ratio [PR]= 1.68; 95% Confidence Interval [CI]=1.19-2.37) and ≥ 60 y.o age group (PR = 1.76; 95%CI = 1.20-1.41). Besides, the residents who do not eat fruits and vegetables daily (PR=1.20; 95%CI=1.01-1.41) and practice less physical activity (PR=1.25; 95%CI=1.01-1.56) were more likely to have central obesity. The productive age group and elderly are at a higher risk for central obesity in an urban slum. Although notable as the main risk factors for central obesity, less consumption of fruits, vegetables and lack of physical activity highlight the urgent need to provide affordable, healthier options for urban slum dwellers.